En busca del autor perdido. Algunas reflexiones sobre el contexto histórico-filosófico del Comentario Anónimo al Tetrabiblos de Tolomeo. - Caballero-Sánchez, José Raúl (Ediciones Clásicas, 2019)
The aim of this paper is to examine the strong formal and structural similarities that bind the Anonymous Commentary to Ptolemy’s Tetrabiblos (Anon. in Ptol.) to the set of commentaries produced by Ammonius and his disciples at Alexandria between the fifth and the sixth centuries. There are indeed some relevant features shared by all of these works: 1) the occasional use of ὁ παλαιός to mean the author of the commented text; 2) the systematic practice of the ‘double discussion’ technique (προθεωρία / λέξις); 3) common exegetical wordings and phrases. All of these features, I claim, strongly suggest that Anon. in Ptol. might well have been a minor product of the post-Ammonius Alexandrian Neoplatonic school.
Keywords: Astrología - Obras anteriores a 1800; Ptolemy; Anonymous Commentary; Tetrabiblos; Greek Astrology; Alexandrian School of Neoplatonism